Pengaruh E-WOM dan Kualitas Produk Terhadap Keputusan Pembelian Cream Blush Wardah Colorfit di Kota Surabaya - Amalia Amin, Rizky; Soebiantoro, Ugy; Mandasari, Virginia (Jurnal Riset Pendidikan Ekonomi, 2025)
A major factor in Indonesia's booming cosmetics and beauty industry is people's increasing awareness of the power of makeup as a means of self-expression, creativity, and confidence boost. Examining how E-WOM and product quality affect consumers' decisions to buy Wardah Colorfit cream blush in Surabaya is the aim of this study. One hundred and forty residents of Surabaya were given questionnaires as part of the quantitative research approach. Non-probability sampling with a purposive approach was the sampling method employed. Using SmartPLS software version 3.0, the PLS method was used for data analysis. With a P value of 0.000 (below the 0.05 threshold) and a path coefficient of 0.344, the analysis's findings show that the E-WOM variable significantly and favorably influences purchasing decisions. With a path coefficient of 0.457 and a P value of 0.000 (<0.05), the product quality variable also demonstrated a significant positive influence on purchasing decisions.This means that the better the content uploaded on social media, the better the consumer's purchasing decision. Meanwhile, the better the product quality, the more influential it is on the purchasing decision. These findings emphasize the importance of E-WOM and good product quality, which impact the consumer's decision-making process